2011
DOI: 10.1103/physrevb.84.060511
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale phase separation in the iron chalcogenide superconductor K0.8Fe1.6Se

Abstract: Advanced synchrotron radiation focusing down to a size of 300 nm has been used to visualize nanoscale phase separation in the K 0.8 Fe 1.6 Se 2 superconducting system using scanning nanofocus single-crystal X-ray diffraction. The results show an intrinsic phase separation in K 0.8 Fe 1.6 Se 2 single crystals at T< 520 K, revealing coexistence of i) a magnetic phase characterized by an expanded lattice with superstructures due to Fe vacancy ordering and ii) a non-magnetic phase with an in-plane compressed latti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
235
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 247 publications
(249 citation statements)
references
References 41 publications
14
235
0
Order By: Relevance
“…The dopant-rich puddles of ordered dopants have been clearly observed also in iron chalcogenide superconductors and it has been shown that the two structural units have a quite different electronic structure with a superconducting or a magnetic phase. [25][26][27] In the underdoped regime of cuprates a structural phase separation between a dopant-poor antiferromagnetic phase and a dopant-rich metallic phase with doping close to 1/8 is clearly observed in La 2 CuO 4+y for 0< y <0.055 28 and YBa 2 Cu 3 O 6+y . 29 In the optimum and high doping regime of cuprates recent high-resolution ARPES and STM experiments [30][31][32] show multiple electronic components with electronic phase separation at low temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The dopant-rich puddles of ordered dopants have been clearly observed also in iron chalcogenide superconductors and it has been shown that the two structural units have a quite different electronic structure with a superconducting or a magnetic phase. [25][26][27] In the underdoped regime of cuprates a structural phase separation between a dopant-poor antiferromagnetic phase and a dopant-rich metallic phase with doping close to 1/8 is clearly observed in La 2 CuO 4+y for 0< y <0.055 28 and YBa 2 Cu 3 O 6+y . 29 In the optimum and high doping regime of cuprates recent high-resolution ARPES and STM experiments [30][31][32] show multiple electronic components with electronic phase separation at low temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Very recent NMR measurements have detected clear signals from a majority magnetic phase as well as a minority superconducting one. 19 The appearance of phase separation occurring at nanometer scales has been detected by Mössbauer, 20 X-ray, 21 and in-plane optical spectroscopy measurements. 22 Scanning Tunneling Microscopy (STM) has been used to image this nanoscopic phase separation directly in epitaxially grown films.…”
mentioning
confidence: 99%
“…More specifically, for example, microbeams have been used for mapping weak diffuse scattering in the real space in Scanning micro X Ray Diffraction (SµXRD) measurements. The collected data, treated by spatial statistical tools, have shown the formation of fractal patterns of interstitial oxygens ordered domains in LCO [21], intrinsic phase separation in doped iron-chalcogenides [22,23] and planar symmetry breaking in Bismuthates [24]. More recently, it's has been demonstrated that the quenched disorder due to dopants is spatially anticorrelated with electronic textures and/or local lattice distortions in Hg1201 [12,13] and LCO [25].…”
mentioning
confidence: 99%